Tindak Lanjut Putusan Mahkamah Konstitusi yang Bersifat Konstitusional Bersyarat Serta Memuat Norma Baru - Ali, Mohammad Mahrus; Hilipito, Meyrinda Rahmawaty; Asy’ari, Syukri (Jurnal Konstitusi, 2015)
The research is concerning the implementation of verdict stating conditionally constitutional, conditionally unconstitutional and and the verdicts that contain new norm decided by Constitutional Court in the case of judicial review of laws againts the 1945 Constitutions of The Republic of Indonesia. This is a juridical-normative research using secondary data in the form of primary law materials, namely the court decisions which are issued throughout the year 2003 up to the year 2012 that have been collected in previous research. This research aims to know the choice of form of law taken by the addressee of the Constitutional Court verdict in following up the three variant of verdicts mentioned above. The research found that the choice of the form of law in implementing the three variants of Constitutional Court verdict is very diverse. Referring to the form and substance of the implementing rules and regulations of the three variants of verdict, there are still some incoherence with  the Constitutional Court verdict which is characterized by the presence of rejudicial review of norms that had been interpreted by the court. To address this problem,  the Constitutional Court must be provided with legal instruments, among other, judicial order that enable the Constitutional Court to order by force the addressee  to implement the Constitutional Court verdict. In addition, in order that to ensure the harmonization of legislation either vertically or horizontally as a result of the Constitutional Court verdict, then it is worth putting into consideration to expand the authority of the Constitutional Court to review all rules and legislation.